Motivation factors for lifelong learning - Trygub, Inna (My University, 2014)
Many aspects of effective teaching apply to all age groups. Understanding the principles of adult learning can help teachers become better facilitators of learning. The importance of these principles is recognized in educational and business settings. This article discusses the differences in how adults learn.
Keywords: навчання дорослих; adult education; мотиваційне навчання; motivational training; кафедра ділової іноземної мови та міжнародної комунікації